Communicative Parenting Workshop in the Digital Era : Reducing Challenges and Finding Solutions for Parents and Early Childhood Children - Ida Nurhaida; Puspandari Setyowati Sugiyanto; Andi Windah; Hestin Oktiani; Sugiyanta Sugiyanta (Bulletin of Social Studies and Community Development, 2025)
The use of gadgets and internet access opens up great opportunities to obtain educational content, enriching children's cognitive stimulation and creativity. However, a series of studies shows that digital parenting interventions practices and strategies parents use to maximize benefits while minimizing the risks of their children's interaction with digital media still face various challenges, especially during early developmental stages. Data from the Operational Curriculum of TK AN-NUR Sabah Balau Tanjung Bintang Lampung Selatan indicates that literacy including digital literacy is considered a basic need in the learning and communication process. This community service aims to reduce children's dependence on gadgets by enhancing parents' digital literacy, strengthening dialogic communication between parents and children in the digital context, raising awareness and skills related to digital safety and health, and integrating local values into digital parenting practices. The activities are carried out in two stages: Focus Group Discussions (FGD) involving interactive dialogues between the service team and participants to identify their initial knowledge about communicative parenting, and training sessions that provide comprehensive knowledge and understanding of communicative parenting for early childhood in the digital era, particularly in facing the challenges posed by the digital world. Evaluation results from pre-tests and post-tests showed a significant improvement in participants' understanding after the training. Before the training, most participants were in the very low understanding category, but after the training, the majority improved their knowledge, with 76.92% of participants in the 'adequate' understanding category and 23.08% in the 'good' category. No participants were in the 'very low' or 'low' category after the training, indicating the success of the program in making a tangible impact.     Keywords: communicative parenting, challenges and solutions, early childhood.